Implementation of lean manufacturing in SMEs using fuzzy analytical hierarchy process - Shilvi Adetia; Muthia Roza Linda (Operations Management and Information System Studies, 2021)
This study aims to analyze: priority weights of driving factors in the application of Lean manufacturing in Kripik Balado Mahkota. This research is classifiied as descriptive research which analyzes the effect of several variables on other variables. The population in this study were all employees at UMKM of Kripik Balado Mahkota, totaling 15 people. In this study, the number of samples was determined using a purpose sampling technique. Purposive Sampling is intended to determine information that represents a number of information needed in the study, so that the sample are the owner and 4 employees in the production sector. The method used in the Analytical Hierarchy Process (AHP) and Fuzzy AHP. This study indicate that the alternative driving factor for the implementation of lean manufacturing with the highest global weight is the criteria of QM 3/ waste analysis which has a weight of 0,11 using AHP and criteria of QM 5/ Total Quality Management which has a weight of 0,05 with fuzzy AHP. The main criteria has the best weight is quality management with weight of o,41 using AHP and 0,22 using fuzzy AHP.